Mineralogy and Fixation Isotherms to Evaluate Phosphorus Needs of Wet and Dry Land Rice Soils in the Bambalang-Ndop Plain in the North West Region of Cameroon - Mbene, Kenneth; Asongwe, Godswill A.; Nkoh, Jackson N.; Njikam, Soulemane N.; Fomenky, Norbert N.; Bame, Irene B. (European Journal of Applied Sciences, 2023)
The sorption processes of Phosphorus (P) in soils contribute to important problems in agriculture. The Mineral structure of the clay fraction plays an important role in soil P adsorption, but its influence on P sorption remains unclear and needs to be elucidated to improve the ability to effectively manage soil P. The aim of this research was to investigate the influence of mineralogy on P fixation. The study was carried out on three wet land and one dry land soil. Soil samples were characterised for their physicochemical and mineralogical properties using standard methods. Soil phosphorus adsorption isotherms were determined with the batch sorption technique by equilibrating 5.00 g of soil samples with 25 ml of KH2PO4 containing 0, 10, 50, 100, 250, and 500 mg P/L. 0.01M CaCl2 background solution. Our results indicated that the wetland soils were dominated by geothites, while the dryland was rich in monthmorillonite, as revealed by the mineralogical analysis. In addition to Ca, exchangeable acidity, organic matter, clay, and pH influenced P fixation; other soil properties such as CEC and exchangeable Na also contributed significantly. The results were interpreted with the Langmuir and Freundlich isotherms, with the Freundlich modes giving the best fit for the adsorption data. The amount of P available in all soils was far below the adequate limit (25 mg P kg-1). Fixation of P was site-specific and revealed that soils can adsorb up to 333.33 mgPkg-1. Therefore, it can be concluded that the Freundlich isotherm should be used to monitor P, thereby minimizing P losses and maximizing crop yield and water quality.